2018
DOI: 10.29252/jhs.6.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Service Quality Gap between Perceptions and Expectations of Service Recipients using SERVQUAL Approach in Selected Hospitals in Golestan Province

Abstract: Background and purpose: Services quality is an important factor of satisfaction, as well as a remarkable tool for marketing to achieve the competitive differentiation and promotion of customer's loyalty. The present study was aimed to analyze the quality gap using SERVQUAL approach at selected hospitals in Golestan Province at the year 2015. Materials and Methods: A cross-sectional survey was conducted on 361 patients of selected hospitals of Golestan Province. To determine sample size, Cochran's sample size f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…In agreement with our study, previous studies conducted in Iran demonstrated that it was a gap between the management intern nursing students' expectations of physical resources, the facilities and equipment of the ward and ideal conditions and also the students believed that creativity of the head of the ward was effective for managing the department due to the lack of both the personnel and the facilities, but they did not consider these conditions to be effective for the management intern nursing students' learning (Tehranineshat et al, 2022;Hoseini-Rostami et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with our study, previous studies conducted in Iran demonstrated that it was a gap between the management intern nursing students' expectations of physical resources, the facilities and equipment of the ward and ideal conditions and also the students believed that creativity of the head of the ward was effective for managing the department due to the lack of both the personnel and the facilities, but they did not consider these conditions to be effective for the management intern nursing students' learning (Tehranineshat et al, 2022;Hoseini-Rostami et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, all Boloso Bombe public health institutions must pay particular attention to the quality of the counseling services provided and strive to provide quality counseling overall. This study was similar to the studies conducted in the different parts of the countries; 7 , 29 , 32 , 35 however, it contradicted the studies conducted in Poland 24 and Nigeria. 36 A possible explanation for this inconsistency could be inequality in facility structure, provider training and experience, and sociodemographic characteristics.…”
Section: Discussionsupporting
confidence: 86%
“…18,27,28,30,31 High quality of counseling service-The resulting SERVQUAL score is positive when performance exceeds expectation (P > E). 32 Satisfactory quality of counseling service-SERVQUAL score is zero (E = P) when perceived (performed) counseling service is equal to expected counseling service. 29 Low quality of counseling service-When SERVQUAL score is negative (E > P), then the performance does not meet the client's expectation.…”
Section: Measurementsmentioning
confidence: 99%
“…The public sector’s desire for quality service delivery emerges with the rise of people’s living standards, technology, and awareness that oblige policymakers and decision-makers to shift their focus toward quality services rather than larger quantities of low-quality services [ 6 ]. It is equally important to note that the quality of service is a matter of concern in the health sector since negligence in improving healthcare service may cause serious outcomes, including an increase in mortality rate, dissatisfaction with healthcare services, and the community members may reject to utilize the public healthcare services [ 4 , 7 ]. Thus, countries worldwide, both developing and developed countries, are striving jointly to build health systems to attain quality [ 2 ].…”
Section: Introductionmentioning
confidence: 99%